2016
DOI: 10.1039/c6ra01933a
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric properties and potential nitro derivatives sensing by a highly luminescent of Zn(ii) and Cd(ii) metal–organic frameworks assembled by the flexible hexapodal ligand, 1,3,5-triazine-2,4,6-triamine hexaacetic acid

Abstract: The luminescent quenching of coordination polymers 1 and 2 were especially obvious with the increasing of the nitro derivatives concentration, indicating 1 and 2 have very high sensitivity sensing properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…A semiempirical absorption correction was applied by the program SADABS . The program suite SHELXTL‐97 was used for space‐group determination (XPREP), direct method structure solution (XS), and least‐squares refinement (XL) . All non‐hydrogen atoms were refined with anisotropic displacement parameters.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…A semiempirical absorption correction was applied by the program SADABS . The program suite SHELXTL‐97 was used for space‐group determination (XPREP), direct method structure solution (XS), and least‐squares refinement (XL) . All non‐hydrogen atoms were refined with anisotropic displacement parameters.…”
Section: Methodsmentioning
confidence: 93%
“…Relative to other nitrogen‐containing ligands (such as pyridine, schiff base, imidazole), carboxylic acid ligands have great advantages. Since carboxylic acids are extremely sensitive to pH, the different degree of deprotonation of the carboxyl groups at different pH values results in different coordination modes (Figure ) . Carboxylic acid groups have a strong ability to bridge, which can take either double‐dentate bridging or single‐dentate bridging.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,5-Triazine-2,4,6-triamine hexaacetic acid (H 6 TTHA) has six flexible carboxylate arms and can adopt a variety of conformations and coordination patterns based on the geometric requirements of different metal ions. The self-assembly of the H 6 TTHA ligand and Zn(II)/Cd(II)/-Cu(III)/Co(II)/rare earth ions has afforded lots of intriguing MOFs with interesting luminescent and magnetic properties [13][14][15]. In view of the unique structural characteristic and multifunctional coordination sites of the H 6 TTHA ligand, in this work, the interaction between Co(II) ions and H 6 TTHA was completed under the hydrothermal condition which is expected to synthesize new functional MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the diversity of coordination, hexacarboxylic acid could react with transition metal ions and nitrogen-containing ligands to form a variety of spatial topologies. Li and colleagues designed and synthesized two new CPs using 1,3,5-triazine-2,4,6-triamine hexa-acetic acid, and both coordination polymers had very high sensitivity to sensing properties at very low concentrations of nitro derivatives [33]. Song and coworkers synthesized three new coordination polymers with H 6 L and different ligands and indicated that these compounds displayed high-sensitivity luminescent sensing functions for nitrobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules 2019, 24, x FOR PEER REVIEW 2 of 13 nitro derivatives [33]. Song and coworkers synthesized three new coordination polymers with H6L and different ligands and indicated that these compounds displayed high-sensitivity luminescent sensing functions for nitrobenzene.…”
Section: Introductionmentioning
confidence: 99%